2020
DOI: 10.1186/s43168-020-00009-y
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of ultrasound-guided, single session pleurodesis in malignant pleural effusion

Abstract: Background Chemical pleurodesis is frequently indicated to relieve symptoms imposed by large/recurrent malignant pleural effusion (MPE). Traditionally, a drain is left in the pleural space till the cessation of fluid accumulation before pleurodesis. Chest ultrasound can detect an amount of pleural fluid as less as 50 ml and can confirm apposition of the pleural surfaces which is required for successful pleurodesis. This work assessed the efficiency and safety of ultrasound-guided, single-session pleurodesis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
3
1
Order By: Relevance
“…These results agreed with Farouk et al [32] who found that 60% of patients with MPE were males and 57% patients were smokers. To the contrary, Magdy and Hieba [14] reported that 75% were females, and this discrepancy as regards gender in comparison to our study may be attributed to their small sample size.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…These results agreed with Farouk et al [32] who found that 60% of patients with MPE were males and 57% patients were smokers. To the contrary, Magdy and Hieba [14] reported that 75% were females, and this discrepancy as regards gender in comparison to our study may be attributed to their small sample size.…”
Section: Discussioncontrasting
confidence: 99%
“…Also, in concordance, Farouk et al [32] found a significant reduction (p˂0.001) in lung sliding among all scanned areas by TUS after povidone iodine pleurodesis. One month after pleurodesis, the iodopovidone group showed the lowest mean lung sliding score in comparison to the spontaneous, tetracycline solution, and tetracycline powder groups (3.35±1.8, p=0.031) Magdy and Hieba [14] illustrated that 2 weeks after doxycycline pleurodesis, absent lung sliding in more than 6 areas was found in 58.8% of cases and mentioned 14.27 ± 2.02 mean Pleural Adherence Score in cases of successful pleurodesis and Pleural Adherence Score of ≥11 after 24h from pleurodesis had sensitivity 93% and 50% specificity. Chaddha et al [37] agreed to the current results and illustrated a Pleural Adherence Score ˃ 10 showed a sensitivity of 100% and specificity of 86% for the prediction of pleurodesis success.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations